Penafsiran Sosiologis Pengamatan Konflik Januari-Mei 1999 - Kusuma Sp., - (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
A minor incident in Ambon has easily trigerred a massive and long lasting conflict. This, from a sociological account, is understandable given the fact the community has suffice condition for explosiive conflict. As the triggering accident come about the conflict was either escalating or leaving potentialfor future conflict.